A quantitative study of pollarding process in silvopastoral systems of Northern Zagros, Iran - Khedri, Laila; Ghahramany, Loghman; Ghazanfari, Hedayat; Pulido, Fernando (Forest Systems, 2017)
Aim of study: This research attempts to quantitatively describe the pollarding process in the northern Zagros, western Iran.Material and methods: An inventory of all trees was conducted in three representative stands in the pollarded section (DBH ≥ 5 cm): DBH, total height, trunk height and crown diameters were measured. At the time of pollarding, 10% of the foliage stacks were randomly selected and weighed. The positions of each store tree (i.e. special trees capable of enduring the weight of a certain number of leafy branches (average 600 kg)) and horizontal distance of pollarded trees associated with each store tree was recorded.Main results: The number and weight of foliage stacks resulting from pollarding of each tree correlated (0.48 and 0.43, respectively) with their crown diameter. The average dry weight of leaf biomass was 1,525.6 ±108.1 kg/ha and there was a significant difference between the selected stands. The average pollarded area and the average number of trees in the pollarded area of each store tree was 501.1±210.4 m2 and 9.4±3.5 trees, respectively.Research highlights: The number of pollarded trees associated with each store tree and the weight of stored foliage stacks on them are determined by the distance between pollarded trees and store trees, the number of trees around the store trees and the ability of selected store trees to bear the weight of foliage stacks.